Effects of Copper Sources and Levels on Nursery Pig Growth Performance - J. A. De Jong; L. Bailey; J. M. DeRouchey; M. D. Tokach; R. D. Goodband; S. S. Dritz (Kansas Agricultural Experiment Station Research Reports, 2015)
A total of 225 pigs (PIC 327 × 1050, initially 25.5 lb) were used in a 21-d trial to evaluate the effects of copper source and level on nursery pig growth performance. Pens of pigs were balanced by initial BW and randomly allotted to 1 of 5 dietary treatments with 9 replications per treatment. The 5 corn and soybean meal-based diets were arranged in a 2 × 2 + 1 factorial with main effects of copper source — copper sulfate (CuSO4) or tribasic copper chloride (TBCC) — and copper level (100 or 200 ppm) with a negative control. From weaning to 25 lb, pigs were fed a common phase 2 diet with added Zn and Cu levels of 1,965 and 17 ppm, respectively. Overall (d 0 to 21), no copper source × level interactions (P>0.10) were observed for any growth criteria. There were also no effects (P>0.10) of copper, copper level, or copper source. These data suggest that adding high levels of copper from either CuSO4or TBCC to late nursery diets did not result in improved performance. Additional research should be conducted to determine if a late nursery Cu response is dependent on Zn concentrations in earlier diets.
Keywords: copper sulfate; nursery pig; tribasic copper chloride